Hydrolysis of cellulose catalyzed by novel acidic ionic liquids. (22nd January 2015) - Zhuo, Kelei; Du, Quanzhou; Bai, Guangyue; Wang, Congyue; Chen, Yujuan; Wang, Jianji
Highlights: Six novel SO3 H-ionic liquids based on 2-phenyl-2-imidazoline were synthesized. Acidic ionic liquids were used as catalysts for cellulose hydrolysis in [Bmim]Cl. Yield of total reducing sugar was dependent on IL's acidity, amount of water. Acidic ionic liquids with anion HSO4 − showed superior catalytic activity. Abstract: The conversion of cellulosic biomass directly into valuable chemicals becomes a hot subject. Six novel acidic ionic liquids (ILs) based on 2-phenyl-2-imidazoline were synthesized and characterized by UV–VIS, TGA, and NMR. The novel acidic ionic liquids were investigated as catalysts for the hydrolysis of cellulose in 1-butyl-3-methylimidazolium chloride ([Bmim]Cl). The acidic ionic liquids with anions HSO4 − and Cl − showed better catalytic performance for the hydrolysis of cellulose than those with H2 PO4 − . The temperature and dosage of water affect significantly the yield of total reducing sugar (TRS). When the hydrolysis of cellulose was catalyzed by 1-propyl sulfonic acid-2-phenyl imidazoline hydrogensulfate (IL-1) and the dosage of water was 0.2 g, the TRS yield was up to 85.1% within 60 min at 100 °C. These new acidic ionic liquids catalysts are expected to have a wide application in the conversion of cellulose into valuable chemicals.